Immune aging in annual killifish - Gabriele Morabito; Alina Ryabova; Dario Riccardo Valenzano (Immunity & Ageing, 2024)
Abstract Turquoise killifish (Nothobranchius furzeri) evolved a naturally short lifespan of about six months and exhibit aging hallmarks that affect multiple organs. These hallmarks include protein aggregation, telomere shortening, cellular senescence, and systemic inflammation. Turquoise killifish possess the full spectrum of vertebrate-specific innate and adaptive immune system. However, during their recent evolutionary history, they lost subsets of mucosal-specific antibody isoforms that are present in other teleosts. As they age, the immune system of turquoise killifish undergoes dramatic cellular and systemic changes. These changes involve increased inflammation, reduced antibody diversity, an increased prevalence of pathogenic microbes in the intestine, and extensive DNA damage in immune progenitor cell clusters. Collectively, the wide array of age-related changes occurring in turquoise killifish suggest that, despite an evolutionary separation spanning hundreds of millions of years, teleosts and mammals share common features of immune system aging. Hence, the spontaneous aging observed in the killifish immune system offers an excellent opportunity for discovering fundamental and conserved aspects associated with immune system aging across vertebrates. Additionally, the species' naturally short lifespan of only a few months, along with its experimental accessibility, offers a robust platform for testing interventions to improve age-related dysfunctions in the whole organism and potentially inform the development of immune-based therapies for human aging-related diseases.